Steroid therapy in patients with inflammatory bowel disease complicating diabetes diagnosis - Knop-Chodyła, Kinga; Piasecka, Zuzanna; Kochanowska-Mazurek, Anna; Głaz, Aneta; Wesołek, Ewelina; Rudzki, Grzegorz (Quality in Sport, 2024)
Inflammatory bowel diseases (IBDs), such as Crohn's disease (CD), ulcerative colitis (UC) or type 1 diabetes (T1D) are autoimmune diseases that may have common susceptibility pathways. In the etiology of these diseases, scientists are seeking not only genetic, but also environmental factors, infections, nutritional deficiencies, and iatrogenic causes, especially in T1D. The relationship between T1D and steroid therapy, used in the treatment of the inflammatory bowel disease, has been well established for years. Steroids are most commonly known for causing drug-induced diabetes. We present a 35-year-old man, in whom a drug-induced diabetes was suggested due to a 4-week steroid therapy used as a treatment for his newly diagnosed ulcerative colitis and a literature review describing a similar problem. To confirm the association between diabetes and steroid therapy, it was necessary to rule out an autoimmune background of the disease. However, the presence of autoantibodies to GAD and anti-α tyrosine phosphatase (IA-2) confirmed the diagnosis of T1D. Aim of the study This review aims to present the issue of type 1 diabetes in patients treated with steroid therapy for inflammatory bowel disease, and to summarize the current state of knowledge, so that in the future it will result in an accurate diagnosis and implementation of appropriate treatment. Methods and materials A literature review was conducted based on the PubMed database, using keywords: ”diabetes mellitus”, ”inflammatory bowel diseases”, ”ulcerative colitis”, „steroids”, ”insulin”. Conclusion We should suspect T1D in patients, especially in the young population suffering from autoimmune diseases in order to prevent serious complications including dysfunction and failure of various organs, such as eyes, kidneys, nerves, heart and blood vessels.